Efficacious removal of mercury metal in food industry sewerage utilizing reduced graphene oxide adsorbent composited with magnetic nanoparticles - Adel Beig Babaei; Arash Dara; Hanieh Sadat Taheri (South African Journal of Chemical Engineering)
This study examines the effectiveness of a composite material made from reduced graphene oxide (rGO) and magnetic nanoparticles for the adsorption of heavy metals from wastewater, addressing a critical environmental issue as heavy metal pollution poses significant risks to human health. Traditional water treatment methods often fail to adequately remove these persistent contaminants. The composite takes advantage of graphene's high surface area and adsorption capacity, while the magnetic nanoparticles facilitate easy separation and reusability of the adsorbent. Characterization techniques such as X-ray diffraction (XRD) and Raman spectroscopy were employed to confirm the composite's structural integrity and the presence of rGO, highlighting its functional properties. The study's focus lay on investigating mercury removal efficiency across varying pH levels (1–6), temperatures (25 °C), mercury concentrations (10 g/L), adsorbent amounts (0.01–0.05 g/L), and contact times (120–360 s). The findings indicated that optimal mercury adsorption occurred at pH 6, with a 100 s contact time, 25 °C, and 0.05 g of adsorbent. The maximum mercury removal achieved was quantified at 9.15 µg/L, demonstrating the potential of iron nanoparticle-magnetized nano graphene oxide as an efficient and sustainable solution for heavy metal remediation in wastewater treatment applications. The results obtained showed that graphene oxide magnetized with iron nanoparticles can be effectively used to remove mercury from water and wastewater samples.Overall, this research highlights a promising pathway towards addressing the pressing challenge of water pollution with heavy metals.